The degree of possessing reflective thinking skills in mathematics among intermediate school students in Al-Qunfudhah Governorate - Al-Jadaani, Ibrahim Abdullah; Al-Zahrani, Khaled Saeed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reflective thinking skills in mathematics required for intermediate school students in Al-Qunfudhah Governorate. Knowing the degree of possessing reflective thinking skills in mathematics among intermediate school students in Al-Qunfudhah Governorate. The research applied the descriptive survey method. The study sample consisted of (352) intermediate school students from (16) schools of the 65 intermediate schools in Al-Qunfudhah Governorate. The schools were randomly chosen. The results showed that the degree to which third-grade students of the intermediate stage in Al-Qunfudhah governorate possessed the skill of visual vision came with a medium degree, with an average of (3.08) and a relative weight (61.53%); the degree of their possession of the skill of coming to conclusions in mathematics came with a medium degree, with an average of (2.55) and a relative weight (50.91%); the degree of their possession of the giving convincing explanations skill in mathematics came with a medium degree, with an average of (3.03) and a relative weight (60.68%); while the degree of their possession of the skills of detecting fallacies and developing proposed solutions in mathematics came with a low degree, with an average (2.20), and a relative weight (44.03%), average (2.11) and relative weight (42.27%), respectively. In general, the degree of possessing reflective thinking skills in mathematics among third-grade students intermediate school students came with a medium degree, with an average of (2.60) and a relative weight (51.88%). These skills are arranged according to their percentages in ascending order as follows: (Detecting fallacies - developing proposed solutions – coming to conclusions - giving convincing explanations - visual insight). Based on the study results, the researcher recommended that teaching thinking in general and reflective thinking in particular shall be included in university courses, especially those of the Faculties of Education that graduate teachers, and training teachers on mechanisms to develop reflective thinking skills among their students through appropriate programs or activities.
Keywords: degree of possession; thinking; reflective thinking; reflective thinking skills